La Cour européenne des droits de l’homme et le traitement de la connaissance scientifique sur la nocivité des ondes électromagnétiques, produits chimiques et autres activités polluantes - Elisabeth Lambert Abdelgawad (VertigO)
This article offers a critical approach of the ways the European Court of Human rights deals with scientific knowledge or its lack in the cases linked to healthy and environmental issues. It shows that the Court adopts two types of strategies : (1) the easiest one occurs when unanimous national studies have concluded to a risk and a causal link or when the thresholds have been clearly exceeded ; (2) the more difficult cases are connected to ongoing scientific controversy and/or uncertainty. In such cases the ECtHR, surprisingly, does not even attempt to seek truth beyond the information given by the respondent State and, taking the easiest way out, hides behind the margin of appreciation doctrine. This study questions the continuation of the causal link and mostly the refusal of a Court of human rights to deliver justice by refusing to equip itself with the scientific information in view of dealing with the cases brought before it by victims looking for justice.